2014
DOI: 10.1038/ejhg.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

Common variant rs10033900 near the complement factor I gene is associated with age-related macular degeneration risk in Han Chinese population

Abstract: Abbreviations: CNV, choroidal neovascularization; GA, geographic atrophy. Data are presented as the mean ± s.d. with range (minimum to maximum). a The remainder of the cases (27.4%) were diagnosed with age-related macular degeneration, but we could not acquire specific subtype information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In our study, although the C allele frequency distribution was not statistically significant, it was higher in the patient group than in the control group. In another study conducted in a Chinese population in which 288 patients with advanced wet-and dry-type AMD and 387 healthy controls were examined, the relationship between CFI rs10033900 polymorphism and AMD was confirmed, but the C allele was reported to be a risk-increasing factor, similar to what we report in our study [24].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, although the C allele frequency distribution was not statistically significant, it was higher in the patient group than in the control group. In another study conducted in a Chinese population in which 288 patients with advanced wet-and dry-type AMD and 387 healthy controls were examined, the relationship between CFI rs10033900 polymorphism and AMD was confirmed, but the C allele was reported to be a risk-increasing factor, similar to what we report in our study [24].…”
Section: Discussionsupporting
confidence: 89%
“…A total of 197 AMD patients (age, 74.87 ± 6.88; female percentage, 43.15%) and 259 unrelated healthy individuals (age, 67.61 ± 6.57; female percentage, 54.44%) were recruited from Putuo People's Hospital, Zhoushan, China (Table 1), and were also used in our previous studies (Qian et al, 2014;Kan et al, 2014Kan et al, , 2015. All of the participants were enrolled concurrently from 2007 to 2008 and were of Han Chinese origin.…”
Section: Subjectsmentioning
confidence: 99%
“…AMD is becoming a major global public health issue, and it presents itself as a complex disease caused by genetic and environmental factors. Studies have shown that environmental factors, such as increasing age (Klein et al, 1997;Friedman et al, 2004) and cigarette smoking (Seddon et al, 1996;Tomany et al, 2004), have risk impacts on AMD, and multiple susceptible genetic loci, which primarily regulate the complement, lipid, angiogenic, and extracellular matrix pathways, also contribute to AMD, such as CFH (Edwards et al, 2005;Klein et al, 2005), C3 (Yates et al, 2007;Maller et al, 2007) and CFI (Fagerness et al, 2009;Qian et al, 2014), APOE (Souied et al, 1998;McKay et al, 2011), LIPC (Neale et al, 2010) and TIMP3 (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The full texts were then evaluated, and 198 additional articles were excluded due to duplication (154), meta-analysis or systematic analysis (28), only case group (4), and no data for each genotype (12). Finally, 11 different articles [23][24][25][26][27][28][29][30][31][32][33] were included in our meta-analysis, including 12 case-control studies about CFI gene rs10033900 polymorphism and total AMD risk and 3 case-control studies about rs2285714 polymorphism and AMD risk. The available clinical information in all publications were shown in Supplementary Table S1.…”
Section: Study Searching and Their Basic Informationmentioning
confidence: 99%